Safety evaluation of variable speed limit system in British Columbia. Issue 10 (6th October 2022) - El Esawey, Mohamed; Sengupta, Joy; Babineau, John E.; Takyi, Emmanuel
Abstract: This study reports the safety benefits associated with the installation of Variable Speed Limit System (VSLS) on provincial highways in British Columbia (BC), Canada. A VSLS is an intelligent transportation system (ITS) that aims at increasing the safety level on highways by varying the speed limit according to downstream operational condition and/or weather conditions. The analysis made use of police-attended serious crashes (i.e. fatal + injury) that took place during winter seasons. Three winter seasons were available as a before-implementation period, and three winter seasons were available as an after-implementation period. The results of a simple-before-and-after showed overall reductions of 35.8% and 36.8% in winter serious collision (WSC) frequency and rate, respectively, were found for the evaluation corridors. An Empirical Bayes (EB) before-and-after safety evaluation was also carried out to ensure that the results are reliable. The EB analysis showed an overall reduction of 34.4% in WSC. An economic assessment of the system was undertaken and the results showed that the benefits of implementing a VSLS exceeded the system cost with an overall benefit-cost (B/C) ratio of 4.3 and a Net Present Value (NPV) of C34.41 million. The results of this study may motivate stakeholders who are interested in pursuing similar systems for mitigating weather-related safety challenges.